The Leopard's Drum - Souhami, Jessica (Frances Lincoln Ltd, 1995)
Osebo the leopard has a fine drum, a huge drum, a magnificent drum. All the animals covet Osebo$1 (Bs drum, but he won$1 (Bt let anyone else have it, not even Nyame, the Sky-God. So, Nyame offers a big reward to the animal that brings him the drum. All try $1 (Bthe monkey, the elephant, even the python $1 (Band all fail. Can a very small tortoise succeed in outwitting the boastful leopard? s
Keywords: Juvenile literature-Fiction